2014
DOI: 10.1016/j.jcsr.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold research — A review

Abstract: Scaffold research -a review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 114 publications
(135 reference statements)
0
27
0
1
Order By: Relevance
“…A comprehensive review and summary of the research from the last forty years on the construction of scaffolds has been presented by the author of paper [2]. Very interesting in the context of this work is the study described in the work [3].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review and summary of the research from the last forty years on the construction of scaffolds has been presented by the author of paper [2]. Very interesting in the context of this work is the study described in the work [3].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11][12][13] conducted research on cuplock-type scaffolds using the probability-based design method. Beale et al [14][15][16], Ao et al [17], Yue et al [18] and Liu et al [19][20] conducted systematic studies on stability capacity and design method of multi-span coupler-type steel-tube scaffold using experimental research and numerical analysis. Engineering accident analysis shows that unstable connection performance of joints is the main cause of scaffold collapse [21].…”
Section: Introductionmentioning
confidence: 99%
“…Romera et al [13] observed that many construction accidents are caused by deficiencies in the project design phase. Beale [14] published a review of scaffolding and falsework structures performed over the last 40 years; this review also discussed the finite element modeling and testing procedures of scaffolds and provided recommendations for modeling connections and different loads on scaffolding systems. Kim and Teizer [15] developed a rule-based system that could automatically plan scaffolding systems for pro-active management in building information modeling.…”
Section: Introductionmentioning
confidence: 99%